2020
DOI: 10.1093/geroni/igaa057.1853
|View full text |Cite
|
Sign up to set email alerts
|

Links Between Rumination and Sleep Quality Among Older Adults: An Examination of the Role of Social Support

Abstract: Rumination is a maladaptive coping strategy that gives rise to and sustains stress. Individuals who ruminate more, therefore, tend to sleep more poorly. Studies of rumination and sleep often neglect the role of social context. Social support may buffer the degree to which rumination predicts poorer sleep quality. Further, individuals with more support may ruminate less, resulting in better sleep quality. Finally, rumination may also erode social support, resulting in poorer sleep quality. The current study tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The aim of this study was to investigate the association between anxiety, social support, coping style and sleep quality among Chinese parents of special children during the early COVID-19 epidemic. The Frontiers in Psychology frontiersin.org result found anxiety was significantly positively correlated with sleep quality, which was consistent with previous studies (Augner, 2011;Liu et al, 2021;Simonetti et al, 2021;Yin et al, 2021), and showed that social support also related to sleep quality closely, which was consistent with previous studies (Brummett et al, 2006;Nordin et al, 2012;Marini et al, 2020;Mitchell et al, 2022). This study found that coping style and its subscale "positive coping style" were not correlated with sleep quality, but the subscale "negative coping style" was positively correlated with sleep quality, which was partially consistent with previous studies (Zhao et al, 2006;Xue et al, 2012;Gao and Hu, 2021;Luo et al, 2022;Yu et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The aim of this study was to investigate the association between anxiety, social support, coping style and sleep quality among Chinese parents of special children during the early COVID-19 epidemic. The Frontiers in Psychology frontiersin.org result found anxiety was significantly positively correlated with sleep quality, which was consistent with previous studies (Augner, 2011;Liu et al, 2021;Simonetti et al, 2021;Yin et al, 2021), and showed that social support also related to sleep quality closely, which was consistent with previous studies (Brummett et al, 2006;Nordin et al, 2012;Marini et al, 2020;Mitchell et al, 2022). This study found that coping style and its subscale "positive coping style" were not correlated with sleep quality, but the subscale "negative coping style" was positively correlated with sleep quality, which was partially consistent with previous studies (Zhao et al, 2006;Xue et al, 2012;Gao and Hu, 2021;Luo et al, 2022;Yu et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Most of studies have found a significant correlation between anxiety and sleep quality, and anxiety is a significant predictor of sleep quality (Augner, 2011;Liu et al, 2021;Simonetti et al, 2021;Yin et al, 2021). Many studies also have shown that social support is related to sleep quality (Brummett et al, 2006;Nordin et al, 2012;Guo et al, 2014;Marini et al, 2020;Mitchell et al, 2022). Some Studies have found positive coping style was negatively correlated with sleep quality (Kong et al, 2021) or not (Zhao et al, 2006), while negative coping style was positively correlated with sleep quality (Kong et al, 2021;Xue et al, 2012) or not (Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Social support refers to the resources available to individuals when needed, which encompasses expressive or instrumental provisions (perceived or received) provided by the community, social networks, and trustworthy individuals, applicable in both everyday scenarios and crises (56)(57)(58). Good social support can make individuals feel the support from society, family, friends, organizations, etc., which can increase positive self-perception, improve their mental health, and provide emotional support (59). Researchers have found that social support has a positive effect on individuals' career development by reducing role pressure at work and increasing job satisfaction and well-being (60,61).…”
Section: Social Support As a Moderating Rolementioning
confidence: 99%